Induction and Escalation Therapies in Multiple Sclerosis - Fenu, G.; Lorefice, L.; Frau, F.; Coghe, G.C.; Marrosu, M.G.; Cocco, E. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2015)
Multiple sclerosis (MS) is a chronic demyelinating disease affecting the central nervous system. Pharmacological therapy of MS includes symptomatic drugs, treatment for relapses (corticosteroid and intravenous immunoglobulin) and disease modifying drugs (DMDs) defined as pharmacological agents that have an impact on relapse rate, disability accumulation and radiological outcomes. Two different therapeutic approaches are widely used in MS: escalation and induction therapy. Escalation therapy consists of an early start with first line DMDs (beta interferon, glatiramer acetate, teriflunomide, dimethyl fumarate) and if DMDs are ineffective or partially effective, switching to second line drugs (mitoxantrone, natalizumab, fingolimod). Induction therapy consists of the early use of immunosuppressant drugs followed by long-term maintenance treatment, generally with immunomodulatory agents. While the use of natalizumab and fingolimod as first line drugs is indicated for aggressive forms of MS, the indication for mitoxantrone as an induction treatment arises from randomized studies demonstrating that induction therapy with mitoxantrone followed by DMD maintenance is more effective than monotherapy with beta interferon. However, the safety profile of induction drugs indicates this is not an acceptable therapeutic strategy for all MS patients in all phases of the disease. The upcoming challenge is to identify patients at high risk of disability development from their clinical characteristics, radiological findings or biomarkers. Furthermore, future studies to establish an individual safety profile stratification are needed.
Keywords: induction therapy